Financial Liberalization, Institutions and Environmental Quality in GCC Countries - Awan, Abdul Basit (Pakistan Journal of Humanities and Social Sciences, 2023)
This paper examines the impact of financial liberalization and institutional factors on the environmental quality in GCC countries, specifically focusing on CO2 emissions. The study employs a panel ARDL model to analyze the link between these variables and environmental quality using data from a pooled mean group of GCC countries spanning the years 1984 to 2021. The study reveals several key findings. Firstly, it establishes a positive association between CO2 emission and democratic accountability. Secondly, corruption is found to hurt environmental quality. Additionally, the research indicates that ethnic conflicts contribute to a rise in CO2 emissions. Moreover, government stability is negatively linked with CO2 discharge. In GCC countries, the results demonstrate a negative connection between high domestic credit granted to the private sector and CO2 release. Furthermore, the study reveals a negative link between CO2 emission and GDP. Foreign direct investment is also shown to have a negative relationship with CO2 emissions, while urbanization and general government final consumption expenditure exhibit a positive relationship with CO2 emissions based on the findings of this research.